2017
DOI: 10.5539/ibr.v10n11p139
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Customer Relationship Management on Long-term Customers’ Loyalty in the Palestinian Banking Industry

Abstract: This paper aims to investigate the impact of customer relationship management on Long-term Customers' Loyalty in the Palestinian banking industry. The data was collected through distributing questionnaires on the Palestinian banking employees. Using multiple regression analysis tests, this paper finds these results; there is a positive and strong linear relationship between dependent variable "long-term customers' loyalty" and CRM, the CRM dimensions are service quality, customer's database, solving customer's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Customer Relationship Management (CRM) is explained as a concept of use process, information, technology, and people to manage the organizations’ interactions with its customers [ 9 ]. By applying efficient and effective CRM technology, CRM employees in SMEs could retain existing customers, attract new customers, foster customer satisfaction, and increase profitability.…”
Section: Customer Relationship Management (Crm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Customer Relationship Management (CRM) is explained as a concept of use process, information, technology, and people to manage the organizations’ interactions with its customers [ 9 ]. By applying efficient and effective CRM technology, CRM employees in SMEs could retain existing customers, attract new customers, foster customer satisfaction, and increase profitability.…”
Section: Customer Relationship Management (Crm)mentioning
confidence: 99%
“…Customer relationship management (CRM) refers to the practices, strategies, and technologies used by firms and businesses for the management and analysis of customer interactions and data through the customer lifecycle [ 7 , 8 ]. It is the concept of using process, information, technology, and people to manage the organization’s interaction with customers [ 9 ]. The technology could be seen as an approach to marketing that has its origins in relationship marketing.…”
Section: Introductionmentioning
confidence: 99%
“…Muro et al (2013) studied the challenges and the strategical benefits of utilizing the customer relationship management systems in the banking industry, they showed that CRM builds robust loyalty relationship with customer if it will be implemented appropriately and it benefits employees, investors and customers. Iriqat and Abu Daqar (2017a) found that there is a positive and strong relationship between CRM and long-term customers' loyalty. Additionally, CRM system integration has a positive direct impact on long-term customers' loyalty.…”
Section: Customer Relationship Managementmentioning
confidence: 98%
“…Skowron and Kristensen (2012) more specifically investigated the impact of financial or banking crises on consumer loyalty in the banking industry, the results show that customers in developing countries have lower loyalty levels than those in developed countries and that financial crises have more substantial effect on customers' loyalty in developing countries. Iriqat and Abu Daqar (2017a) investigated the impact of customer relationship management on long-term customers' loyalty in the Palestinian Banks; they demonstrate that there is a direct impact on long-term customers' loyalty and employees' behavior.…”
Section: Long-term Customers' Loyaltymentioning
confidence: 99%
See 1 more Smart Citation